JEALOUSY, BY ITSELF, DOES NOT CONSTITUTE A BASE MOTIVE (CIPEEX, 2025)
This paper examines whether jealousy, taken alone, can support the qualifying circumstance of a “base motive” (motivo torpe) and when it should instead be treated merely as a factor of violent emotion. It aims to clarify the criminal-law concept of a base motive and to delineate its boundaries vis-à-vis mitigating causes and privileged forms under the Brazilian Criminal Code. Methodologically, it adopts a doctrinal-normative approach grounded on Articles 65(III)(c), 121 §1, and 129 §4, and employs illustrative factual scenarios to assess contextual relevance. The findings indicate that jealousy, standing alone, does not amount to a base motive; despite its blameworthiness, it is linked to affective conflict and the agent’s psychological sphere and should, where the legal requirements are met, be weighed as violent emotion with mitigating or privileging effects. Only when combined with additional, objectively reprehensible circumstances—such as cruel means or ignoble ends—may jealousy support the qualifier; for instance, torture committed out of jealousy reveals heightened censure and may trigger the qualifier. It concludes that subsumption demands an assessment of the full factual record, precluding automatic presumptions.
Keywords: jealousy; base motive; violent emotion; Criminal Law